A divergent lineage among Octopus minor (Sasaki, 1920) populations in the Northwest Pacific supported by DNA barcoding. Issue 4 (21st April 2018) - Xu, Ran; Bo, Qikang; Zheng, Xiaodong
ABSTRACT: Octopus minor (Sasaki, 1920) is an important economic fishery resource in China. In order to explore the stock information and the phylogeographic status of O. minor, mitochondrial DNA cytochrome c oxidase subunit I (COI, 565 bp) and 16S rRNA (493 bp) genes were amplified from 11 different sampling locations. Genetic diversity evaluated by haplotypic and nucleotidic diversity implied high diversity in Lianjiang, and relatively low diversity in Rongcheng, which suggests that effective measures to protect the O. minor resource in this area are urgently required. Private haplotypes and remarkable higher pairwise ΦST in Yilan are responsible for the deep genetic divergence between Yilan and the 10 other populations. Haplotypes networks and two clusters' topological structure also support the distinct subgroups (lineages A and lineages B), which apparently possess smaller genetic variation than mean interspecies distance. Taiwan island and its strait may act as a natural barrier that restricts the gene flow from the mainland. Deep genetic divergence between mainland and Taiwanese east coasts suggests different genetic stock, indicating that different management strategies are required.